2022
DOI: 10.1136/bmjopen-2021-059366
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ acceptance of obesity as a chronic disease: a qualitative study in Lebanon

Abstract: ObjectiveThis study explores patients’ acceptance of obesity as a chronic disease.DesignCross-sectional, qualitative study using semistructured phone interviews.SettingThe study was conducted in specialty and primary care clinics from a single central tertiary hospital in Lebanon. Recruitment took place between February and March 2021.Participants and methods25 adult patients with overweight or obesity were interviewed and the interviews were analysed thematically.ResultsFour themes emerged: (1) patients’ know… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
0
4
0
2
Order By: Relevance
“…16(p418) Several other medical associations and societies have followed suit. 16,28 Viewing obesity as a chronic illness is not new to health care providers, but society continues to view it as a lifestyle choice rather than a disease process. It will take education and time to shift the social stigma of obesity.…”
Section: Obesity As a Chronic Diseasementioning
confidence: 99%
“…16(p418) Several other medical associations and societies have followed suit. 16,28 Viewing obesity as a chronic illness is not new to health care providers, but society continues to view it as a lifestyle choice rather than a disease process. It will take education and time to shift the social stigma of obesity.…”
Section: Obesity As a Chronic Diseasementioning
confidence: 99%
“…El médico familiar que realiza ejercicio generalmente recomienda que su paciente lo haga, lo que incide en romper el comportamiento sedentario, brindando beneficios para otorgar una consulta integral 44 . Se ha notado que si los médicos realizaban mayor cantidad de actividad física, también exponencialmente ofrecían consejos en actividad física a sus pacientes, sobre todo si acudían a consultas subsecuentes para atender enfermedades crónicas 45 . Existe una gran área de oportunidad si los profesionales de salud trabajan de forma colaborativa con programas que estén alineados a necesidades comunitarias locales, reforzando positivamente la prescripción de actividad física y el cuidado de salud poblacional.…”
Section: El Médico Como Ejemplounclassified
“…Al Arab et al 45 reportaron que los pacientes tienen ambivalencia en aceptar el sobrepeso y obesidad como una enfermedad, considerando que el médico tiene un rol únicamente para solucionar complicaciones, así como el manejo es simplemente «comer menos y moverse más», lo cual, según lo analizado, dista mucho del papel que el médico familiar puede tener en la prevención y tratamiento de esta población. Conforme lo comentado previamente, debemos romper esa pasividad y tratar de una forma más dinámica a las personas para obtener mejores resultados.…”
Section: El Médico Como Ejemplounclassified
“…A recent qualitative study in Lebanon reported an ambivalent reaction from persons with obesity to being presented with the chronic disease model of obesity. 29 The purpose of this study was to evaluate the impact of this core story on internalized weight bias and perceived patient-provider relationship in a sample of PwO.…”
Section: Introductionmentioning
confidence: 99%